INVESTIGATING STUDENTS' DIFFICULTIES IN LEARNING LISTENING COMPREHENSION SKILLS AT USWATUN HASANAH SENIOR HIGH SCHOOL - Fadilah, Lailatul; Hifdil Islam, Muhammad; Kholili, Achmad (STKIP PGRI Situbondo, 2024)
This article is written to describe the students' difficulties in learning to listen in class X. This study aims to reveal the difficulties of listening comprehension by students and strategies to overcome listening difficulties in the English class. This research has been conducted at Senior High School, Selogudik Wetan, Pajarakan-Probolinggo. This study used descriptive and qualitative research. This research design refers to the tradition of ethnographic study research. Participants in this research were two student from 16 students. The researcher used the fill-in-the blank strategy to evaluate and validate the data. The researcher conducted observations by collecting data through documentation and conducting interviews with English-language students. The results of this study show that students have difficulties listening and have strategies to overcome these problems. These difficulties include a lack of vocabulary, speaking speed, accent, concentration, and motivation. In addition, the strategy used is to fill in the blank, which involves listening to an audio song and completing the missing lyrics by filling in the vocabulary of the lyrics. The conclusion of the research is that difficulties in listening can hinder student success. As well as strategies that can help students overcome listening difficulties. However, this research is expected to be developed by further researchers. Key Word: student's difficulties; listening comprehension,;EFL learning.